2005
DOI: 10.1007/s11071-005-0044-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Stability Analysis of Thin Viscoelastic Film Flowing Down on the Inner Surface of a Rotating Vertical Cylinder

Abstract: This paper investigates the stability of thin viscoelastic liquid film flowing down on the inner surface of a rotating vertical cylinder by means of the long wave perturbation. After proving the insufficiency of the linear model in characterization of certain flow behaviors, a generalized nonlinear kinematic model is then derived to represent the physical system. This model is solved through the following procedure. In the first step, the normal mode method is used to characterize the linear behaviors. The amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
(27 reference statements)
2
18
0
Order By: Relevance
“…The solutions obtained by deriving the viscoelastic analog of the Orr-Sommerfeld equation with the requisite boundary conditions revealed that viscoelastic effects tend to destabilize the film flow. A similar finding was reported by Chen et al [4] in their nonlinear stability analysis of a thin viscoelastic liquid film flowing down the internal surface of a rotating vertical cylinder.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…The solutions obtained by deriving the viscoelastic analog of the Orr-Sommerfeld equation with the requisite boundary conditions revealed that viscoelastic effects tend to destabilize the film flow. A similar finding was reported by Chen et al [4] in their nonlinear stability analysis of a thin viscoelastic liquid film flowing down the internal surface of a rotating vertical cylinder.…”
Section: Introductionsupporting
confidence: 87%
“…(25)-(30), the governing equations of the thin-film system can be collected and solved on an order-by-order basis. In practice, the non-dimensional surface tension, S n , has a large value, and thus the term α 2 S n can be treated as a zeroth-order quantity [3][4][5]. Furthermore, for y h, the film thickness h is very small, using the power series solution ϕ = ∞ n=0 k n y n about 0, and hence power series approximation solutions can be obtained up to the order of y 5 at the zeroth-and first-orders of the stream function (given in Appendix A).…”
Section: Generalized Kinematic Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This last fluid model was also used by Shaqfeh et al (1989) including moderate Reynolds numbers and in the non linear problem by Joo (1994) with an extra viscous thinning effect and by Kang and Chen (1995). The nonlinear stability of a Walters B fluid model of a thin film down a flat wall was investigated by Cheng et al (2000) and this was extended for the case of a vertical cylinder only taking into account the axial modes Cheng et al (2001). However, the instability using an Oldroyd B fluid model has not been investigated.…”
Section: Introductionmentioning
confidence: 99%